IMPLEMENTATION ONLINE SINGLE SUBMISSION SYSTEM IN INCREASE PUBLIC SERVICES AT THE INVESTMENT AND SERVICES OFFICE INTEGRATED ONE-STOP SERVICE (DPMPTSP) REGENCY SIDOARJO - Putri, Ardita Kirana; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Online Single Submission (OSS) system at the Investment and Integrated One-Stop Services Office (DPMPTSP) of Sidoarjo Regency in enhancing the quality of public services, particularly in the business licensing process, using George C. Edward III’s four indicators of communication, resources, disposition, and bureaucratic structure. Method: A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation. Informants were selected using purposive sampling, consisting of DPMPTSP officials and business actors utilizing the OSS system. Data analysis applied the Miles and Huberman model, covering stages of reduction, presentation, and conclusion. Results: Findings indicate that OSS implementation is relatively effective in expediting business licensing and improving transparency; however, challenges remain, including limited external communication with vulnerable groups, insufficient technical training due to budget constraints, and inadequate bureaucratic adaptability to central regulation changes. Despite these limitations, the proactive disposition of implementers plays a crucial role in supporting success. Novelty: The contribution of this study lies in applying Edward III’s theoretical framework to the local context of Sidoarjo while offering practical recommendations to strengthen inclusive communication, sustainable training, and bureaucratic flexibility as strategies to optimize OSS in the future.